IMPRESSION IN EXTENDED PARTIALLY EDENTATION - IMPLICATIONS IN METHODS OF TRAINING FOR DENTAL TECHNICIANS - Magda-Ecaterina Antohe; Monica Andronache; Roxana Ionela Vasluianu; Cosmin Ionuț Crețu; Ovidiu Stamatin; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2019)
In practice, we want to be as effective in time and achievement, but impressions must be carried out with the utmost attention to detail and dedication to perfection, because it is a mirror of what we want to do. THE PURPOSE of this study is to identify the clinical peculiarities of the different types of impression used in the partially stretched edentation with profound impact in the technological algorithm and in the end of the therapeutic solution approached in the territory of partially removable prosthesesMATERIAL AND METHOD Different types of impressions have been analyzed and materialized in the clinical algorithm of a rehabilitative technique in the partial stretching, dictated by the specificity of the clinical case. Knowing the technological particularities according to the clinical stages is an important demand of this study.RESULTS AND DISCUSSIONS Regarding the use of techniques and materials in practice, several studies have been conducted to observe the choices of practitioners and the methods used in dental schools in the world. In the last decade, the development of fully digitized techniques in all areas of dental medicine began. CONCLUSIONS Functional impression is a particularly important clinical stage with profound impact on the final development of prosthesis